Striatal cholinergic interneurons in isolated generalized dystonia—rationale and perspectives for stem cell-derived cellular models - Capetian, Philipp; Pauly, Martje Gesine; Azmitia, Luis Manuel; Klein, Christine (Frontiers in Cellular Neuroscience, 2014)
Interneurons comprise a minority of the striatal neuronal population of roughly 5%. However, this heterogeneous population is of particular interest as it fulfills an important relay function in modulating the output of the only type of striatal projection neurons, i.e., the medium spiny neuron (MSN).One subtype of this heterogenous group, the cholinergic interneuron, is of particular scientific interest as there is a relevant body of evidence from animal models supporting its special significance in the disease process. The development of protocols for directed differentiation of human pluripotent stem cells (PSC) into striatal interneurons provides a unique opportunity to derive in vitro those cell types that are most severely affected in dystonia.In this review we first aim to give a concise overview about the normal function of striatal interneurons and their dysfunction in dystonia in order to identify the most relevant interneuronal subtype for the pathogenesis of dystonia. Secondly we demonstrate how knowledge about the embryonic development of striatal interneurons is of particular help for the development of differentiation protocols from PSC and by this depict potential ways of deriving in vitro disease models of dystonia. We furthermore address the question as to whether cell replacement therapies might represent a beneficial approach for the treatment of dystonia.